2011
DOI: 10.5551/jat.5983
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Cardio-Ankle Vascular Index and Microvascular Complications in Type 2 Diabetes Mellitus Patients

Abstract: Aim: Type 2 diabetes mellitus (T2DM) is a risk factor for increased arterial stiffness. We evaluated associations between the cardio-ankle vascular index (CAVI) and carotid plaque, intima media thickness (IMT), and diabetic microvascular complications in Korean T2DM patients. Methods: We conducted a retrospective, cross-sectional study of 320 Korean T2DM patients without a history of macrovascular disease or macroalbuminuria. We measured 24-hour urinary albumin excretion (UAE) levels and performed funduscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 34 publications
2
65
0
1
Order By: Relevance
“…Moreover, previous studies have established a strong association between the CAVI and small-vessel disease of other organs. 23,24 Kubozono et al 23 reported a relationship between the CAVI and a low estimated glomerular filtration rate. Kim et al 24 identified a correlation between the CAVI and microvascular complications in type 2 diabetes mellitus patients without a history of macrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies have established a strong association between the CAVI and small-vessel disease of other organs. 23,24 Kubozono et al 23 reported a relationship between the CAVI and a low estimated glomerular filtration rate. Kim et al 24 identified a correlation between the CAVI and microvascular complications in type 2 diabetes mellitus patients without a history of macrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Kubozono et al 23 reported a relationship between the CAVI and a low estimated glomerular filtration rate. Kim et al 24 identified a correlation between the CAVI and microvascular complications in type 2 diabetes mellitus patients without a history of macrovascular disease. The CAVI may thus be a marker of small-vessel disease of various organs, including the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxia, hypercapnia and pressure surges accompanying intermittent hypoxia events may also serve as potent stimuli for the release of vasoactive substances, leading to impairment of the endothelial function. Moreover, a low oxygen level is a trigger for the activation of neutrophils, which adhere to the endothelium ), physical activity (mets · hr/day), smoking (y/n), alcohol consumption (y/n), hypertension (y/n), DM (y/n), and hyperlipidemia (y/n) Furthermore, we used the CAVI, a reliable, reproducible and novel marker of arterial stiffness 26,31) . Limitations of this study include the fact that the cross-sectional design cannot be used to establish causality between NIH, arterial stiffness and an overweight status.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a CAVI of ≥ 9 have been reported to present with significantly higher mean and maximum intima-media thicknesses, carotid beta stiffness indices and levels of carotid plaque 31) . Furthermore, it has been reported that a cut-off CAVI value of 8.81 yields maximum sensitivity and specificity for detecting coronary artery disease.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation